Do practitioner assessments agree with academic proxies for audit quality? Evidence from PCAOB and internal inspections - Aobdia, Daniel (Journal of Accounting and Economics, 2019)
This study investigates the degree of concordance between fifteen measures of audit quality used in academia and two measures of audit process quality determined either by audit firms’ internal inspections or by Public Company Accounting Oversight Board inspections of individual engagements. Using two confidential datasets of these assessments of audit process quality, I find that three of the measures of audit quality used by academics have significant associations with both measures of audit process deficiencies used by auditors and regulators: (i) the propensity to restate financial statements, (ii) the propensity to meet or beat the zero earnings threshold, and (iii) audit fees. Seven academic proxies are significantly associated with only one audit process quality measure, and five have insignificant associations with both practitioner assessments. Overall, the significant associations indicate that practitioners and academics share common ground in identifying low-quality audits. These findings can provide guidance for future studies in selecting audit-quality proxies suitable for different research questions.